2012
DOI: 10.1016/j.bone.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, body mass index and bone mineral density—associations in a prospective population-based cohort of women and men: The Canadian Multicentre Osteoporosis Study (CaMos)

Abstract: Background-Physical activity (PA) is an important modifiable risk factor for both bone mineral density (BMD) and body mass index (BMI). However, BMI is itself strongly predictive of BMD. Our aim was to determine the association between PA and BMD, with consideration of BMI as a potential mediating factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
77
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 30 publications
(34 reference statements)
15
77
0
6
Order By: Relevance
“…In addition to DEXA, osteoporosis examination can be done with BMI [16]. Overweight and obesity have been considered protective to bone health, while higher BMI levels to be associated with higher BMD score [17][18][19][20]. In this study, the height and weight were positively correlated with BMD and the same result.…”
Section: Discussionsupporting
confidence: 50%
“…In addition to DEXA, osteoporosis examination can be done with BMI [16]. Overweight and obesity have been considered protective to bone health, while higher BMI levels to be associated with higher BMD score [17][18][19][20]. In this study, the height and weight were positively correlated with BMD and the same result.…”
Section: Discussionsupporting
confidence: 50%
“…However, the mean weight and BMI values of the two groups of patients did not differ significantly. Other studies have also shown an association between body weight (14,15) and BMI (1,11,22,(30)(31)(32)(33) with BMD. But, Saravi et al (4) reported no significant effect of BMI on BMD.…”
Section: Discussionmentioning
confidence: 87%
“…Interpretation of areal BMD, an indicator of bone strength, is challenging in obese subjects, as it associates strongly with BMI and lean mass [2,3]. Despite high BMD, obese subjects have an increased risk of fractures, especially in lower extremities and peripheral sites [4][5][6].…”
Section: Introductionmentioning
confidence: 98%